2012
DOI: 10.1248/cpb.c12-00149
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Particle Size and Dispersion State among Commercial Cyclosporine Formulations and Their Effects on Pharmacokinetics in Rats

Abstract: Generic versions of Neoral, a microemulsion capsule formulation of cyclosporine, have been approved worldwide. However, there are concerns about the quality and efficacy of the generics due to the formulation specificity and differences in inactive ingredients among products. In this study, we measured the physicochemical properties of both the innovator and the generic formulations, and compared their bioavailability in rats. When the capsule contents were dispersed in water, the absorbance (600 nm wavelength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…It has been reported that certain non‐innovator immunosuppressive products used in several countries do not exhibit equivalent pharmaceutical properties with regard to innovator products . Such formulations should not be considered as generics.…”
mentioning
confidence: 99%
“…It has been reported that certain non‐innovator immunosuppressive products used in several countries do not exhibit equivalent pharmaceutical properties with regard to innovator products . Such formulations should not be considered as generics.…”
mentioning
confidence: 99%
“…Aggregation size is generally smaller than crystallization size; therefore, the results of (A) and (I) could be attributed to aggregation rather than crystallization. Moreover, in past study, the particle size of Sandimmun ® formulation dispersed in water was measured, and it was reported that the mean particle size was approximately 1400 nm [ 26 ]. This finding is likely because of aggregation, which could also be attributed to results (A) and (I), although the cause of occurrence of aggregation could not be determined in this study.…”
Section: Discussionmentioning
confidence: 99%
“…17 This may be due to different types of solubilizers that are generally used in original and generic products. 6,7,19 Although in vitro dissolution test is routinely used to confirm the possibility of human bioequivalence, the actual impact of absorption behavior of solubilizers on drug dissolution cannot be detected by the in vitro tools and might be one of the reasons for the difficulty to develop bioequivalent oral products of BCS class II drugs.…”
Section: Discussionmentioning
confidence: 99%
“…30 However, it is well known that particle size and dispersion state of microemulsion are greatly influenced by the concentration of oil, solvents, and/or surfactants in the dispersed medium. 19 The bio-inequivalence of commercial microemulsion capsules of cyclosporine, a BCS class II drug, has been reported. 19,[34][35][36] Because these products contain different solvents and surfactants, 19 the different absorption behavior of these components may have led to the bioinequivalence of the cyclosporine products.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation